Deixis Analysis in Audio Material of English for Nusantara untuk SMP/MTs Kelas VIII Textbook - Riosepriyatna, Riosepriyatna; Rezeki, Yanti Sri; Wardah, Wardah (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
This research focuses on the concept of deixis within pragmatics, specifically examining the audio materials of the English for Nusantara untuk SMP/MTs Kelas VIII textbook used for teaching the English language in Indonesia. Deixis involves using language to point to specific entities or characteristics within a given context. The study aims to identify the various types of deixis present, determine the dominant types employed, and describe the reference meanings associated with deixis in the materials. Through qualitative descriptive research and content analysis methods, the study identifies three primary deixis categories within the audio material: Person Deixis (56.76%), Temporal Deixis (30.63%), and Spatial Deixis (12.61%). The dominant use of Person Deixis underscores its importance and role in language use within the educational materials. These findings contribute significantly to a deeper understanding of deixis in language learning contexts, emphasizing its pragmatic significance and relevance in instructional materials.